1997
DOI: 10.1161/01.atv.17.11.2617
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Enlargement in Coronary and Femoral Arteries Is Related to Neither the Extent of Plaque-Free Vessel Wall Nor Lesion Eccentricity

Abstract: Arteries may demonstrate compensatory enlargement in response to plaque accumulation. It has been proposed that enlargement is achieved by the expansion of the nondiseased (plaque-free) vessel wall. In this study, we assessed this hypothesis. Post mortem, 32 atherosclerotic coronary arteries (left anterior descending, n = 10; left circumflex, n = 11; and right coronary, n = 11) and 54 atherosclerotic femoral arteries were pressure fixed. Cross sections (coronary arteries, n = 537; femoral arteries, n = 1602) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…dilatory response. This effect would be anticipated to be least pronounced in the plaque-related vessel wall because of endothelial dysfunction, thereby explaining the observation of some investigators, though not all, 25 that outward remodeling is more prominent in the setting of eccentric than concentric plaques. 4,10 Conversely, Glagov et al, 1 using detailed geometrical characterization of human coronary arteries, concluded that the dilatory response is mainly associated with outward bulging beneath plaques.…”
Section: Expansive Remodeling Is a Local Plaque-related Phenomenonmentioning
confidence: 97%
“…dilatory response. This effect would be anticipated to be least pronounced in the plaque-related vessel wall because of endothelial dysfunction, thereby explaining the observation of some investigators, though not all, 25 that outward remodeling is more prominent in the setting of eccentric than concentric plaques. 4,10 Conversely, Glagov et al, 1 using detailed geometrical characterization of human coronary arteries, concluded that the dilatory response is mainly associated with outward bulging beneath plaques.…”
Section: Expansive Remodeling Is a Local Plaque-related Phenomenonmentioning
confidence: 97%
“…This cut-off value was based on earlier histological data [19] and IVUS study [20], that also used this criterion to discriminate between presence and absence of plaque. Plaque free wall (PFW) was defined as the arc of the vessel wall having a wall thickness<0.5 mm [19,20] expressed in degrees: PFW ¼ 360 means totally healthy, PFW ¼ 0 means disease with more than 0.5 mm wall thickness over the complete circumference. To determine the PFW on IVUS (IVUS-PFW), the circumference was subdivided into 32 equidistant angles and at each angle the wall thickness was evaluated.…”
Section: Intravascular Ultrasound Analysismentioning
confidence: 99%
“…It is perhaps because eccentric atherogenesis frequently originates at sites of low or turbulent flow that also impairs outward remodeling that postmortem studies have found no relationship between remodeling and lesion eccentricity or extent of disease-free arc. 41 …”
Section: Clinical Observations Regarding the Mechanisms Of Atherosclementioning
confidence: 99%